Surface Sterilization to Isolate Fungal Root Endophytes of Meranti Tembaga (Shorea leprosula Miq.) in Dramaga Experimental Forest - Safinah S. Hakim S Hakim; Sri Wilarso Budi; Maman Turjaman (Jurnal Silvikultur Tropika, 2014)
Root fungal endophyte were isolated from seedling of Meranti Tembaga (Shorea leprosula Miq.) taken from Dramaga experimental Forest, Bogor with five difference surface sterilization methods. Recommended surface sterilization to isolate root fungal endophyte was performed by following immersion process : 96% ethanol for 1 min, 20% H2O2 for 3 min, 96% ethanol for 0.5 min, and rinse with sterile water for 5 min. Endophyte frequency was low (6-11%) and four morphological types of fungi were found during this research.